Deteksi Dini Penyakit Melalui Screening Kesehatan Gigi dan Mulut pada Anak-Anak di Rumah Asuh YABNI Padang - Hanim Khalida Zia; Sevilla Ukhtil Huvaid (Yayasan Literasi Sains Indonesia, 2023)
According to Riskesdas 2018, the prevalence of people experiencing dental and oral diseases in Indonesia has increased sharply from 23.2% in 2007 to 57.6% in 2018. The problem found at the YABNI Padang Orphanage was that many children complain of toothache, there have been no dental and oral examinations for children. The solution offered by the head of the proposing team was to carry out early detection of disease through dental and oral health screening for children at the YABNI Padang Orphanage. It was hoped that promotive and preventive efforts will be achieved against dental and oral health risks for children at the YABNI Padang Orphanage by implementing dental and oral health screening for children as well as educating administrators and children about how to care for children's teeth and mouth. Apart from that, the planned output target in this community service was research articles in national service journals. From the results of this community service, it was found that early detection of dental and oral cases/diseases, the most common being caries/cavities, was 101 cases, with 62 cases in girls and 39 cases in boys. Managers should provide ongoing education to foster children so that they remained aware of the importance of dental and oral health.